Acoustics of Emotional Prosody Produced by Prelingually Deaf Children With Cochlear Implants - Chatterjee, Monita; Kulkarni, Aditya M.; Siddiqui, Rizwan M.; Christensen, Julie A.; Hozan, Mohsen; Sis, Jenni L.; Damm, Sara A. (Frontiers in Psychology, 2019)
Purpose: Cochlear implants (CIs) provide reasonable levels of speech recognition in quiet, but voice pitch perception is severely impaired in CI users. The central question addressed here relates to how access to acoustic input pre-implantation influences vocal emotion production by individuals with CIs. The objective of this study was to compare acoustic characteristics of vocal emotions produced by prelingually-deaf school-age children with cochlear implants (CCI) who were implanted by age 2 and had no usable hearing before implantation with those produced by children with normal hearing (CNH), adults with normal hearing (ANH), and postlingually-deaf adults with cochlear implants (ACI), who developed with good access to acoustic information prior to losing their hearing and receiving a CI. Method: A set of 20 semantically emotion-neutral sentences were recorded by 13 CCI, 9 CNH, 9 ANH and 10 ACI, each with a Happy and a Sad emotion, without training or guidance. The sentences were analyzed for primary acoustic characteristics of the productions. Results: Significant effects of Emotion were observed in all acoustic features analyzed (mean voice pitch, standard deviation of voice pitch, intensity, duration and spectral centroid). ACI and ANH did not differ in any of the analyses. Of the four groups, CCI produced the smallest acoustic contrasts between emotions in voice pitch and in its standard deviation. Effects of developmental age (highly correlated with duration of device experience) and age at implantation (moderately correlated with duration of device experience) were observed, as well as interactions with the children’s sex. Conclusion: Although prelingually deaf CCI and postlingually deaf ACI are listening to similarly degraded speech and show similar deficits in vocal emotion perception, these groups are distinct in their productions of contrastive vocal emotions. The results underscore the importance of access to acoustic hearing in early childhood for the production of speech prosody, and also suggest the need for a greater role of speech therapy in this area.